El juego infantil para corregir problemas de lenguaje en niños de preparatoria de la escuela Dr. Edison Calle Loaiza de la ciudad de Loja, periodo académico 2018-2019 - Mora Guevara, Leidy Gisselle (2020)
The research work entitled THE CHILD GAME TO CORRECT LANGUAGE PROBLEMS IN PREPARATORY CHILDREN SCHOOL DR. EDISON CALLE LOAIZA OF LOJA CITY, ACADEMIC PERIOD 2018-2019, has as general objective to determine the children's game to correct pronunciation difficulties in high school children; on the literature review the topics related to children's game and language problems were addressed; the following methods were used in the research process: the scientific, descriptive, inductive, deductive and statistical method; the technique used was a survey applied to high school teachers; the Maria Melgar test was applied to children, which evaluates phonetic acquisition, phonetic construction and articulation development, and the dyslalia evaluation protocol, section evaluation of the oral and phonemic organs to rule out anomalies that prevent language development; among the weighted results we can highlight the existence of a significant percentage of children with problems in the articulation of some phonemes, symphones and diphthongs; In order to contribute to the correction of the difficulties, the alternative proposal "Playing and singing is getting better" was planned and implemented; a significant conclusion reached by the research process, is that children's play is a strategy that favors the reduction of pronunciation difficulties, so teachers are recommended to use effective methods for the timely correction of these problems.